Global Policy vs. Local Reality: Resolutions Implementation and Challenges for Child Protection in Armed Conflicts - Hastira, Muhammad Fajhriyadi; Sartika, Dewi; Ahmad, A Aliyah; Muhammad, Ali (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This study aims to evaluate the effectiveness of child protection policies implemented by UNSC permanent member states through various resolutions (including Resolutions 1612/2005 and 2764/2024) and to identify the impediments to the implementation of these resolutions that stem from the interests of UNSC permanent member states and internal institutional factors. The present study employs a qualitative methodology with an analytical approach, utilizing secondary data collected from various official documents, including UNSC Resolutions, the annual reports of the UN Secretary-General, UNICEF publications, and relevant academic journal articles. The literature review included an analysis of previous research on child protection, UNSC policy effectiveness, and implementation challenges on the ground. The study reveals that the UNSC has endeavored to address this conflict through Resolutions 1612/2005 and 2764/2024. However, the implementation of these resolutions has frequently encountered various dynamics from the UNSC's permanent members, including the rejection of external intervention, political compromise in decision-making, geopolitical factors, and constraints within the UNSC institution that can impede effectiveness. This study employs thematic analysis to address the existing gap in understanding the issue of children in armed conflict, particularly those perpetrated by the UNSC through Resolutions, and the role of UNSC Permanent Members.